Click to Chat

1800-2000-838

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```        prove that:
i. cosec2A - cot2A = tanA
ii. 2sinAcos3A - 2sin3AcosA = sin4A/2```
6 years ago

510 Points
```										1) COSEC2A - COT2A = TANA
LHS= 1/SIN2A - COS2A/SIN2A
=1-COS2A/SIN2A
COS2A = 1-2SIN2A       &           sin2a =2SINACOSA  ,   BY USING THESE

LHS=  [1- (1-2SIN2A)]/2SINACOSA
=2SIN2A/2SINACOSA=SINA/COSA
=TANA = RHS
HENCE PROVED

```
6 years ago
510 Points
```										2)
2SINACOS3A - 2SIN3ACOSA = SIN4A/2
LHS =2SINACOSA(COS2A - SIN2A)
COS2A - SIN2A =COS2A   &   2SINACOSA =SIN2A
LHS =SIN2ACOS2A
=(2SIN2ACOS2A)/2
=SIN4A/2                                  (using sin2x = 2sinxcosx)
hence proved
```
6 years ago
Saroj Koiry
23 Points
```										Cosec2A= cot2A+tanA=> RHS=cot2A+tanACos2A/sin2A+sinA/cosACos2A*cosA+sin2A*sinA/sin2A.cosaCos(2A-A)/sin2A.cosACosA/sin2A.cosA1/sin2A=cosec2A
```
4 months ago
Think You Can Provide A Better Answer ?

Other Related Questions on Trigonometry

View all Questions »
• Complete JEE Main/Advanced Course and Test Series
• OFFERED PRICE: Rs. 15,900
• View Details